Vibration o f corrugated cross-ply laminated composite plates - Phu, Khuc Van; Dan, Le Van (VNU Journal of Science: Mathematics - Physics, 2007)
A b s t r a c t . ỉn the present paper the governing equations for dynamical analysis of corrugated cross-ply laminated composite plates in the form of a sin vvave are developed based on the KirchoíT-Love^ theory and the extension of Seydel’s technique. The problems of natural vibration and forced vibration of a plate vvith various boundary conditions are studied. EíTects of íactors as geometry dimensions, order of laminate as well as waved-amplitude on írequency of naturaỉ vibration, amplitude of forced vibration of the corrugated cross-ply laminated composite plates are also analysed.